A molecular phylogeny of the snakes of the Philothamnus heterodermus (Hallowell, 1857) (Squamata: Colubridae: Colubrinae) species group with the description of two new species - (:unkn) unknown (My University, 2022)
The molecular phylogeny of specimens from the Philothamnus heterodermus species groupin West and Central Africa reveals important unrecognized specific diversity. In West Africa, four speciesare present: P. heterodermus, P. bellii, P. pobeguini and one cryptic species previously confused withP. carinatus. In Central Africa, five species are present: P. heterodermus, P. carinatus, P. ruandae and twocryptic species, one previously confused with P. carinatus, the second one with P. heterodermus. Here wedescribe two of these three cryptic species: Philothamnus brunneus sp. nov. from the Guinean rainforestof West Africa and Philothamnus mayombensis sp. nov. from the rainforest of the Mayombe mountains inCongo-Brazzaville and Congo-Kinshasa.
Keywords: African Research